2011
DOI: 10.1063/1.3602466
|View full text |Cite
|
Sign up to set email alerts
|

Padé spectrum decompositions of quantum distribution functions and optimal hierarchical equations of motion construction for quantum open systems

Abstract: Padé spectrum decomposition is an optimal sum-over-poles expansion scheme of Fermi function and Bose function [J. Hu, R. X. Xu, and Y. J. Yan, J. Chem. Phys. 133, 101106 (2010)]. In this work, we report two additional members to this family, from which the best among all sum-over-poles methods could be chosen for different cases of application. Methods are developed for determining these three Padé spectrum decomposition expansions at machine precision via simple algorithms. We exemplify the applications of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
210
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 213 publications
(213 citation statements)
references
References 24 publications
1
210
0
Order By: Relevance
“…[34][35][36]. Using the Padé approximant to the Bose-Einstein function in the definition of α j (t) [23] represents α j (t) in the form of Eqn. (6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36]. Using the Padé approximant to the Bose-Einstein function in the definition of α j (t) [23] represents α j (t) in the form of Eqn. (6).…”
Section: Resultsmentioning
confidence: 99%
“…with p jk and γ jk defined by the Padé decomposition that was first introduced in [22], and explained in more detail in [23].…”
Section: Theorymentioning
confidence: 99%
“…[86][87][88] The present simulations employ a tolerance filter for the auxiliary density operators 89 and the [R − 1/R] Padé decomposition scheme. 90 It was found that the calculations converge at R = 4 for the T = 230 K case and R = 5 for the T = 77 K case. Fig.…”
Section: B Excited-state Proton Transfermentioning
confidence: 99%
“…50 Padé points is used in the Padé spectrum decomposition (see Eq. (2)) [24]. Figure 4(a) shows the atomic structure and parition scheme for this combined GNR system.…”
Section: B Graphene Nanoribbon System (Tb Model)mentioning
confidence: 99%